The clinical and radiographic success of Endoflas compared with other root canal obturating materials in primary teeth: A systematic review - Sainath Reddy Elicherla; Sujatha Bandi; Kanamarlapudi Venkata Saikiran; Mahesh Nunna; Putta Sai Sahiti; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2022)
Pulpectomy aims at retaining the tooth in the asymptomatic state until exfoliation. Root canal obturating materials should resorb in synchronization with the primary root and get eliminated rapidly upon accidental extrusion. This systematic review aims at appraising the clinical and radiographic outcomes of Endoflas as an obturating material for primary teeth. An extensive literature search on obturating materials used for primary teeth using MeSH terms in PubMed, Cochrane library, and Ovid® from September 2002 to March 2020. Studies evaluating the clinical and radiographic success of Endoflas as an obturating material in children were included. From 45 retrieved articles, eight qualified for the systematic review. Moderate quality of evidence was elicited in this review. There was a dramatic reduction of inter radicular radiolucency in Endoflas obturated teeth compared to other root canal filling materials. Even for resorption of the extruded material beyond the apex too, Endoflas has depicted a faster clearance rate. Hence,it was concluded that, Endoflas can be a potential root canal obturating material for treating the primary teeth, even with furcal radiolucency. We recommend randomized clinical trials satisfying all the norms of CONSORT guidelines to provide a high quality of evidence.